HISTORICAL ENSEMBLES PRESERVATION IS THE BASIS OF DEVELOPMENT - Juraev Zamon Zubaydulla ogli (Research Parks Publishing LLC, 2020)
This article describes the architectural ensembles transformation of Bukhara gave rise to rich urban planning methods and the architectural traditions formation, architectural ensembles creation, methods and features of their urban structure formation to find modern ways to transform, to pass on the analysis to the next generation while maintaining its status